Importance of Transport Services in Tourism (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The main purpose of this article is that transport is one of the most important components of the economy of any country. Many years ago, man used various means to transport people and goods. With the advent of wheels and other modes of transport, modes of transport such as wagons and steam locomotives began to appear. This person began to travel faster over long distances. At present, transport with a highly developed economic and social base is one of the mechanisms of the state economy.